Adsorption of methylene blue using calcium oxide from chicken eggshell - Unkaew Woravarun; Poka Pinchaphat; Clowutimon Weerawat; Assawasaengrat Pornsawan (E3S Web of Conferences)
The adsorption of methylene blue on calcium oxide synthesized from chicken eggshells was investigated as a method for wastewater purification. Calcium oxide adsorbent was prepared by calcining ground eggshells in a furnace at 900°C for 3 hours, resulting in a material with approximately 97% purity. Adsorption experiments were conducted in batch mode, using a 0.25g: 50 ml ratio of adsorbent to solution and maintaining a temperature of 35°C. The contact time and initial methylene blue concentration were varied between 0-480 minutes and 10-200 mg/L, respectively. Equilibrium was reached within 240 minutes, the adsorption isotherm can be modelled by Langmuir model with a maximum specific amount adsorbed of 27.03 mg/g.